(untitled) (Economics and region, 2024)
The article is devoted to the study of scientific and methodological foundations for assessing ecological and economic risks in the implementation of a model for sustainable development of enterprises under increasing energy challenges. It was determined that the development of a modern business model for enterprises should take into account changes in their competitive position, new trends in the development of the energy market, processes of decentralization of energy networks, and the reconstruction of Ukraine’s energy infrastructure under the influence of geopolitical factors. The authors propose an economic-mathematical model for analyzing the volume of the company’s products, taking into account the value of its products for the consumer. The implementation of this approach will make it possible to determine ways to achieve sustainable energy development of Ukrainian enterprises and their adaptation to new conditions of competitiveness and energy sustainability.